An Atomic View of Cation Diffusion Pathways from Single‐Crystal Topochemical Transformations. (21st July 2020) - Handy, Joseph V.; Luo, Yuting; Andrews, Justin L.; Bhuvanesh, Nattamai; Banerjee, Sarbajit
Abstract: The diffusion pathways of Li‐ions as they traverse cathode structures in the course of insertion reactions underpin many questions fundamental to the functionality of Li‐ion batteries. Much current knowledge derives from computational models or the imaging of lithiation behavior at larger length scales; however, it remains difficult to experimentally image Li‐ion diffusion at the atomistic level. Here, by using topochemical Li‐ion insertion and extraction to induce single‐crystal‐to‐single‐crystal transformations in a tunnel‐structured V2 O5 polymorph, coupled with operando powder X‐ray diffraction, we leverage single‐crystal X‐ray diffraction to identify the sequence of lattice interstitial sites preferred by Li‐ions to high depths of discharge, and use electron density maps to create a snapshot of ion diffusion in a metastable phase. Our methods enable the atomistic imaging of Li‐ions in this cathode material in kinetic states and provide an experimentally validated angstrom‐level 3D picture of atomic pathways thus far only conjectured through DFT calculations. Abstract : Large single crystals of a cathode material have been grown and then discharged (up to high depths of discharge) and then charged without pulverization, providing high‐resolution crystal structures delineating not just lattice sites occupied by Li ions but also the precise atomistic pathways that Li ions traverse through the lattice. The derived angstrom‐level 3D picture of atomic pathways (yellow arrow) has been correlated with electrochemical signatures of the discharge process.